Gene expression profiles of two testicular somatic cell lines respond differently to 4-nitrophenol mediating vary reproductive toxicity. (November 2021) - Wei, Jinhuan; Lu, Tingting; Dong, Fulu; Zhang, Chong; Zhang, Yonghui
Abstract: 4-Nitrophenol (PNP) has been extensively used in manufacturing for several decades. Its toxic effects on the male reproductive system have been reported, but the underlying mechanisms remain unclear. In this study, we utilized two testicular somatic cell lines (TM3 and TM4 cells) to explore the possible toxic effects of PNP on the male reproductive system. The activity of the cells after exposure to different doses of PNP (0.01, 0.1, 1, 10 and 100 μM) was evaluated. PNP treatment at 10 μM significantly inhibited cell viability, and 10 μM PNP was thus selected for subsequent experiments. Although PNP (10 μM) inhibited cell proliferation, promoted cell apoptosis, and changed the cell cycle distribution and ultrastructure in both types of cells, these effects were more significant in the TM4 cells. In addition, an Agilent mouse mRNA array was used to identify the gene expression differences between the control and PNP (10 μM) exposed TM3 and TM4 cells. The microarray analysis identified 67 and 1372 differentially expressed genes mainly concentrated in endothelial cell morphogenesis and anatomical structure development in TM3 cells and associated with cardiovascular system development and circulatory system development in TM4 cells. Moreover, a pathway analysis revealed that PNP not only predominately affected meiotic recombination and meiosis in TM3 cells, but also influenced axon guidance and developmental biology in TM4 cells. These results suggest that TM3 and TM4 cells exhibit different responses to PNP, which might mediate different toxic mechanisms.